Teucrium polium induces apoptosis in peripheral blood lymphocytes isolated from human chronic lymphocytic leukemia - Zarić, Milan; Živković Zarić, Radica; Mitrović, Marina; Nikolić, Ivana; Čanović, Petar; Milosavljević, Zoran; Jovanović, Danijela; Zelen, Ivanka (Vojnosanitetski pregled, 2021)
Background/Aim. Chronic lymhocytic leukemia (CLL) is considered more as a disease of cells accumulation due to the defect in apoptosis rather than deregulated cell’s proliferation. The activation of apoptosis is one of the main molecular mechanisms responsible for anti-cancer activities of most of the currently studied potential anti-cancer agents, including natural compounds.  Teucrium polium (TP) extracts exhibited strong cytotoxic effects in murine leukemia cell line, RAW 264.7 and human melanoma cell line, C32, but their cytotoxic effects against human leukemia cells were unknown. Methods. The viability of human leukemia cell lines (MOLT 4 and JVM 13), lymphocytes isolated from 28 patients with CLL (CLL cells), and peripheral blood mononuclear cells (PBMCs) isolated from 16 healthy subjects treated with TP leaves methanolic extract, was determined by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Apoptosis of TP treated CLL cells was measured by flow cytometry applying Annexin V/7AAD staining. The expressions of active proapoptotic protein Bax, antiapoptotic protein Bcl-2, cytochrome c and the percentage of cells containing cleaved caspase-3 in treated CLL cells was determined by flow cytometry and immunocytochemistry. Results. The TP methanolic extract decreased the viability of all tested human leukemia cells but it had no effect on the viability of PBMCs isolated from healthy subjects. The cytotoxic effect of TP was caused by its induction of CLL cells’ apoptosis. TP disarranged the ratio of the expressions of proapoptotic Bax and antiapoptotic Bcl-2 protein in favor of Bax, consequently inducing apoptosis by cytochrome c mitochondrial release and activation of caspase-3 in treated CLL cells. Conclusion. The TP leaves methanolic induced selective apoptosis in CLL cells and it affected the expressions of key proteins involved in the regulation of programmed cell death.
Keywords: teucrium extract; apoptosis; leukemia, lymphocytic, chronic, b cell; cell line; mice; humans